2005
DOI: 10.1002/jms.844
|View full text |Cite
|
Sign up to set email alerts
|

Proton affinity ladder for uridine and analogs: influence of the hydroxyl group on the sugar ring conformation

Abstract: A ladder of relative proton affinities (PA) for a series of modified uridines (e.g. araU, ddU, 5BrU, 5BrdU and 5IU) was established from competitive dissociations of proton-bound heterodimers using Cooks and co-workers' kinetic method. The studied heterodimers are constituted of a modified nucleoside and either an amino acid or a nucleoside with known PA value. These non-covalent heterodimers were prepared under electrospray conditions to be selected and dissociated into the ion-trap analyzer. These results al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Similarly to uracil and thymine, the calculations [33] at the B3LYP/6-31G* level of theory predict that the O 8 (C 5 ) position is the most preferred protonation site for the most stable uridine and thymidine tautomers, 2, and this position is likely to be the most favorable for water binding, 2a.…”
Section: Uracil and Thymine And Their Nucleosidesmentioning
confidence: 99%
“…Similarly to uracil and thymine, the calculations [33] at the B3LYP/6-31G* level of theory predict that the O 8 (C 5 ) position is the most preferred protonation site for the most stable uridine and thymidine tautomers, 2, and this position is likely to be the most favorable for water binding, 2a.…”
Section: Uracil and Thymine And Their Nucleosidesmentioning
confidence: 99%
“…dUrd is highly susceptible to modification at the 5-position such that minor forms of dUrd with halogen, ethyl, methylthio, hydroxymethyl and allyl substituents are known, and these dUrd variants are used as antiviral drugs. [34][35][36] Tabet and coworkers 37 measured the proton affinities (PAs) of Urd and dUrd using the kinetic method 38 and complemented these measurements with theoretical calculations. They found that the PA of dUrd is B10 kJ mol À1 greater than the PA of Urd, and that the sugar configuration exerts only a minor effect on the PA (B2 kJ mol À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such analytical methods started contributing to PNA structural investigations in 199322 and allowed identification of PNA/DNA23 duplexes, and PNA/DNA/PNA24, 25 triplexes as well as DNA/PNA/DNA (within triplex or duplex invasion configurations) 26. Mass spectrometry efficiently provided information on: (1) thermochemical properties (relative basicity/acidity scales),27–31 (2) the stoichiometry of the noncovalent complexes constituted by DNA and PNA oligomers23, 32 and (3) gas‐phase conformation of oligonucleotide associations by ion mobility33 and by collision‐induced dissociation (CID)34 or blackbody infrared dissociation (BIRD) 35. It is important to note that the hydrogen‐bonding and electrostatic interactions, such as cation–π and π–π,36–44 which impart rigidity to their conformations, are known to be preserved during their transfer from the solution to the gas phase.…”
Section: Introductionmentioning
confidence: 99%